Wasteful Commuting - Hamilton, Bruce W.; Röell, Ailsa (Journal of Political Economy, 1982)
In this paper I examine the ability of the monocentric models to predict the mean length of commute in urban areas. I compare actual mean commute with that which is predicted by monocentric models and find that actual commuting distance is about eight times greater than that predicted by the model. Next I calculate the volume of commuting which would result if people chose their houses and jobs at random, making no effort to economize on commuting. This overpredicts actual commuting by about 25 percent.